Image Fusion for Brain Tumor Diagnosis Using Fractal Weighted Adaptive Dual Channel Neural Network - Mantha, Shailaja; Brahmaiah Naik, Jatothu; Sateesh Kumar, Kanagala; Rajanidevi (Al-Nahrain Journal of Science, 2026)
This research paper proposes a novel image fusion algorithm for assisting effective diagnosis of brain cancers. The method extracts detailed features from source images using a multi-level decomposition strategy that leverages local extrema information. The detailed layers are fused using an Enhanced Weighted Pulse Adaptive Dual Channel Neural Network (EWPADCNN), with fusion weights calculated using the Fractal Dimension with Differential Box Counting (FDDBC) method. In order to preserve low-frequency information, the base layers uses a weighted average method based on pixel significance. Comprehensive tests on 100 slices from four different datasets of brain disorders demonstrates that the proposed approach outperforms current fusion methods in both qualitative and quantitative assessments. These results support the suggested method as an efficient and trustworthy technique for improving brain imaging diagnostic quality. Quantitative evaluation demonstrates average improvements of 41%, 5%, 16%, 23%, 34%, and 4% in terms of AG, H, SF, MI, QABF, and SD metrics, respectively, compared to existing fusion methods.